World scientific production on education and COVID 19: a bibliometric analysis - Postigo Zumarán, Julio Efraín (2022)
The objective of this study is to characterize the world scientific production on education and COVID-19 between the months of January 2020 to September 2021. A bibliometric study was carried out in five databases (Scopus, Web of Science, Google Academic, Microsoft Academic and Crossref) from which a universe of 5005 articles was extracted. The bibliometric indicators were analyzed with the help of the Publish or Perish v. 7.19 and the same analytical software of the chosen databases. Regarding the most cited article published in the analyzed databases, the one entitled "Medical Student Education in the Time of COVID-19" stands out, which received 419 citations in the Scopus database, 368 in Web of Science, 442 in Crossref, 870 in Google Scholar and 702 in Microsoft Academic. Regarding the authors with the highest scientific production on the subject, Maria Assuncao Flores stands out with 5 publications on the Web of Science and Francisco José García-Peñalvo with 5 articles indexed in the Scopus database. Regarding the journals with the highest number of articles on education and COVID-19, Sustainability stands out. These results show that the scientific production referring to education and Covid-19 confirms the radical change generated in education at all levels by the pandemic and the increase in scientific production to try to explore and describe the changing situation resulting from the pandemic in education. Regarding the journals with the highest number of articles on education and COVID-19, Sustainability stands out. These results show that the scientific production referring to education and COVID-19 confirms the radical change generated in education at all levels by the pandemic and the increase in scientific production to try to explore and describe the changing situation resulting from the pandemic in education. Regarding the journals with the highest number of articles on education and COVID-19, Sustainability stands out. These results show that the scientific production referring to education and Covid-19 confirms the radical change generated in education at all levels by the pandemic and the increase in scientific production to try to explore and describe the changing situation resulting from the pandemic in education.